Neural Mechanisms of Emotion Regulation in Autism Spectrum Disorder - Richey, J. Anthony; Damiano, Cara R.; Sabatino, Antoinette; Rittenberg, Alison; Petty, Chris; Bizzell, Josh; Voyvodic, James; Heller, Aaron S.; Coffman, Marika C.; Smoski, Moria; Davidson, Richard J.; Dichter, Gabriel S. (Journal of autism and developmental disorders, 2015)
Autism spectrum disorder (ASD) is characterized by high rates of comorbid internalizing and externalizing disorders. One mechanistic account of these comorbidities is that ASD is characterized by impaired emotion regulation (ER) that results in deficits modulating emotional responses. We assessed neural activation during cognitive reappraisal of faces in high functioning adults with ASD. Groups did not differ in looking time, pupilometry, or subjective ratings of faces during reappraisal. However, instructions to increase positive and negative emotional responses resulted in less increase in nucleus accumbens and amygdala activations (respectively) in the ASD group, and both regulation instructions resulted in less change in dorsolateral prefrontal cortex activation in the ASD group. Results suggest a potential mechanistic account of impaired ER in ASD.